On the relevance of income and behavioral factors for absolute and relative donations: A framed field experiment - Amantia Simixhiu; Andreas Ziegler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Based on data from a computer-based survey among more than 500 German respondents, this paper empirically examines the effect of actual equivalent income and estimated income position as well as behavioral factors on absolute and relative donations. Donations were measured in an incentivized framed field experiment, i.e. the respondents could spend money for three prominent environmental and social organizations. The perceived relative income refers to the estimated percentage of German households with a lower equivalent income compared to the own equivalent income. Furthermore, the behavioral factors are based on experimentally validated survey questions. Our preliminary econometric analysis with Tobit models shows that both actual equivalent income and estimated income position have significantly positive effects on absolute donations, whereby the effect of actual equivalent income is more dominant. This suggests that income perceptions play a minor role for donations compared to actual income. Surprisingly and in contrast to previous studies, income has a solid significantly negative effect on relative donations for all income groups. In addition, negative reciprocity has a significantly negative effect on both absolute and relative donations, which underlines the relevance at least of this behavioral factor. The estimation results also reveal that life satisfaction is significantly positively related with absolute donations. This suggests that positive feelings play an important role for donation activities.
Keywords: C93; D31; D64; H24; H40; 330; Environmental and social donations; behavioral factors; actual equivalent income; estimated income position; Tobit models; framed field experiment